Metabolic syndrome is associated with prognosis in patients with acute ischemic stroke after intravenous thrombolysis: a prospective cohort study - Chen, Wenyan; Liu, Dandan; Li, Zhiqiang; Zhang, Xiaofang (Frontiers in Neurology, 2025)
ObjectiveMetabolic syndrome (MetS) is a known risk factor for stroke, but its impact on prognosis after intravenous thrombolysis (IVT) in acute ischemic stroke (AIS) remains unclear. This study aimed to evaluate the association between MetS and prognosis in AIS patients treated with IVT.MethodsWe conducted a prospective cohort study including AIS patients who received IVT at Shanxi Bethune Hospital between January 2022 and December 2023. Propensity score matching (PSM) was applied to balance baseline characteristics between MetS and non-MetS groups. The primary outcome was 3-month all-cause mortality. Secondary outcomes included good functional outcome (modified Rankin Scale [mRS] 0–2) and symptomatic intracranial hemorrhage (SICH).ResultsAfter PSM, 292 patients (146 pairs) were enrolled in the analysis. The all-cause mortality rate within 3 months was significantly higher in the MetS group compared to the non-MetS group (24.0% vs. 11.6%; p < 0.01). Multivariate Cox regression analysis indicated that MetS was independently associated with increased 3-month mortality (adjusted hazard ratio [HR] = 2.50, 95% CI: 1.35–4.60; p < 0.01). A dose–response relationship was observed between the number of MetS components and mortality. Additionally, patients with MetS were less likely to achieve good functional outcomes (adjusted odds ratio [OR] = 0.47, 95% CI: 0.28–0.77; p < 0.01) and had a higher risk of SICH (adjusted OR = 2.40, 95% CI: 1.17–4.92; p = 0.02).ConclusionMetS is an independent predictor of increased mortality, poorer functional recovery, and higher risk of SICH in AIS patients treated with IVT. Early identification and management of metabolic risk factors may improve outcomes in this population.